Preparation of BT/GNP/PS/PVDF composites with controllable phase structure and dielectric properties. (August 2021) - Liu, Junwang; Zhang, Mingting; Guan, Lizhu; Wang, Chunfeng; Shi, Lei; Jin, Yi; Han, Chao; Wang, Jihua; Han, Zhidong
Abstract: The composite system composed of polymer, conductive and dielectric filler has excellent dielectric properties. Herein, by studying the effect of filler distribution on the composite system's performance, the graphene nanoplatelets/Polystyrene (GNP/PS)/Barium titanate/Polyvinylidene Fluoride (BT/PVDF) selective composite system is prepared. When the conductivity and dielectric loss change little, the dielectric constant and breakdown field strength of the selective composite system are improved obviously. In the selective composite system, as the dielectric constant is between 12 and 13, the characteristic breakdown field strength is as high as 25.8 kV/mm, which is over three times higher than it of the pure composite system. It is because the addition of BT and GNP particles enhances the establishment of polarization. Besides, the blending of PVDF and PS improves the breakdown field strength of the material. Comprehensive properties of the material are enhanced. Therefore, this study provides a basis for the subsequent study of dielectric materials. Highlights: The selective composite system of (graphene plate/polystyrene)/(barium titanate/polyvinylidene fluoride) is prepared. In the selective composite system, the characteristic breakdown field strength is as high as 25.8 kV/mm, which is over three times higher than it of the pure composite system. The dielectric constant of the blend system which has continuous matrix and selective distribution of fillers is predicted by the mixed dielectric model. The theoretical predicted value of the dielectric constant is in good agreement with the measured value.